Carotid Artery Stenting and Intracranial Thrombectomy for Tandem Cervical and Intracranial Artery Occlusions. Issue 2 (8th March 2019) - Kim, Byungjun; Kim, Byung Moon; Bang, Oh Young; Baek, Jang-Hyun; Heo, Ji Hoe; Nam, Hyo Suk; Kim, Young Dae; Yoo, Joonsang; Kim, Dong Joon; Jeon, Pyoung; Baik, Seung Kug; Suh, Sang Hyun; et al.
Abstract: BACKGROUND: It remains controversial whether carotid artery stenting (CAS) is needed in cases of tandem cervical internal carotid artery occlusion (cICAO) and intracranial large vessel occlusion (LVO). OBJECTIVE: To investigate the efficacy and safety of CAS in combination with endovascular thrombectomy (CAS-EVT) in cICAO-LVO patients and to compare its outcomes with those of EVT without CAS (EVT-alone). METHODS: We identified all patients who underwent EVT for tandem cICAO-LVO from the prospectively maintained registries of 17 stroke centers. Patients were classified into 2 groups: CAS-EVT and EVT-alone. Clinical characteristics and procedural and clinical outcomes were compared between 2 groups. We tested whether CAS-EVT strategy was independently associated with recanalization success. RESULTS: Of the 955 patients who underwent EVT, 75 patients (7.9%) had cICAO-LVO. Fifty-six patients underwent CAS-EVT (74.6%), and the remaining 19 patients underwent EVT-alone (25.4%). The recanalization (94.6% vs 63.2%, P = .002) and good outcome rates (64.3% vs 26.3%, P = .007) were significantly higher in the CAS-EVT than in the EVT-alone. Mortality was significantly lower in the CAS-EVT (7.1% vs 21.6%, P = .014). There was no significant difference in the rate of symptomatic intracranial hemorrhage between 2 groups (10.7 vs 15.8%; P = .684) and according to the use of glycoprotein IIb/IIIa inhibitor (10.0% vs 12.3%; P = .999) or antiplatelet medications (10.2% vs 18.8%; P = .392). CAS-EVT strategy remained independently associated with recanalization success (odds ratio: 24.844; 95% confidence interval: 1.445-427.187). CONCLUSION: CAS-EVT strategy seemed to be effective and safe in cases of tandem cICAO-LVO. CAS-EVT strategy was associated with recanalization success, resulting in better clinical outcome.